A new city o/s : The Power of Collaborative, and Distributed Governance - Goldsmith, Stephen, ....-; Kleiman, Neil, ....- (Washington, D.C. : Brookings Institution Press, 2017)
Proposing an entirely new governance model to unleash innovation throughout local government. At a time when trust is dropping precipitously and American government at the national level has fallen into a state of long-term, partisan-based gridlock, local government can still be effective-indeed more effective and even more responsive to the needs of its citizens. Based on decades of direct experience and years studying successful models around the world, the authors of this intriguing book propose a new operating system (O/S) for cities. Former mayor and Harvard professor Stephen Goldsmith and New York University professor Neil Kleiman suggest building on the giant leaps that have been made in technology, social engagement, and big data. Calling their approach distributed governance, Goldsmith and Kleiman offer a model that allows public officials to mobilize new resources, surface ideas from unconventional sources, and arm employees with the information they need to become pre-emptive problem solvers. This book highlights lessons from the many innovations taking place in today's cities to show how a new O/S can create systemic transformation. For students of government, A New City O/S: The Power of Distributed Governance presents a groundbreaking strategy for rethinking the governance of cities, marking an important evolution of the current bureaucratic authority-based model dating from the 1920s. More important, the book is designed for practitioners, starting with public-sector executives, managers, and frontline workers. By weaving real-life examples into a coherent model, the authors have created a step-by-step guide for all those who would put the needs of citizens front and center. Nothing will do more to restore trust in government than solutions that work. A New City O/S: The Power of Distributed Governance puts those solutions within reach of those public officials responsible for their delivery.
Keywords: Openbaar bestuur; Sociologie van het beleid